Relación entre recaudación tributaria y desigualdad de ingresos en el departamento de Loreto, periodo 2007 – 2022 - Tavares Melendez, Patsy Amparo (2024)
This study investigates the relationship between tax collection and income inequality in the department of Loreto, Peru, during the period 2007-2022. Using Spearman's correlation coefficient, quantitative data were analyzed to identify trends and associations between tax collection, the number of taxpayers, the level of unemployment and the Gini Coefficient as a measure of inequality. The results indicated a significant negative correlation between tax collection and income inequality (ρ = − 0.693), suggesting that an increase in collection is associated with a reduction in inequality. Similarly, a negative relationship was found between the number of taxpayers and inequality (ρ=−0.682), which supports the theory that greater inclusion in the tax system promotes economic equity. Furthermore, a moderate negative correlation was observed between tax revenue and unemployment, suggesting that an effective fiscal policy can positively influence the labor market. These findings are aligned with previous studies and emphasize the importance of progressive fiscal policies in the fight against socioeconomic inequality. The research concludes with proposals to improve equity through a more effective and progressive tax system in Loreto.